Finite element modelling of damage fracture and fretting fatigue - Wahab, M. Abdel; Hilmy, Irfan; Hafiz, Tauqeer; Talemi, R. Hojjati (Ghent University, Department of Mechanical construction and production, 2012)
This paper summarises the research carried out to develop Finite Element (FE) modelling and predictive techniques for damage, fracture, fatigue and fretting fatigue problems. A damage model is developed based on Continuum Damage Mechanics and integrated within FE code. It is then used to predict the number of cycles to crack initiation in adhesively bonded joints. Furthermore, crack propagation algorithm is programmed within FE code using the principles of Fracture Mechanics and Paris law. The effect of mode mixity on crack propagation is taken into account using a Double Cantilever Beam (DCB) test specimen. Moreover, FE model of fretting fatigue aluminium test specimen is carried out in order to study the stress distribution and predict the crack propagation fatigue lifetime. Fretting fatigue problems involve two types of analyses; namely contact mechanics analysis and damage/fracture mechanics analysis. Both analyses are performed in FE code and the stress distribution along the contact surface between the two bodies is obtained and analysed. Furthermore, crack propagation analysis under fretting fatigue condition is presented. In most cases, the numerical results are compared to experimental ones.